Hybrid offline programming method for robotic welding systems - Zheng, Chen; An, Yushu; Wang, Zhanxi; Wu, Haoyu; Qin, Xiansheng; Eynard, Benoît; Zhang, Yicha (Robotics and computer-integrated manufacturing, 2022)
•Current automatic programming approaches for robotic manufacturing systems have been reviewed.•A hybrid offline programming method that combines CAD-based and vision-based offline approaches is proposed.•The vision-based and CAD-based activities of the proposed programming method with the support techniques are presented.•Vision & CAD interactive activities are proposed to identify the workplace, detect the deviation, and compensated the path. Offline programming is an intuitive and automatic programming generation technique that does not use real robotic systems, thus greatly decreasing the downtime required for system programming, and resulting in enormous savings in terms of labor costs. Currently, offline programming can be generally categorized into computer-aided-design-based (CAD-based) and vision-based approaches; these two types of offline programming approaches have been widely applied in robotic welding systems. However, owing to the highly complex and diverse workpieces needed in the shipbuilding industry, neither of the aforementioned offline programming approaches can fully support the automatic generation of welding programs. In this paper, a hybrid offline programming method systematically combining CAD-based, vision-based, and vision & CAD interactive activities is proposed to overcome the limitations of current automatic program generation methods for robotic welding systems. In the vision-based activities, the positions of the workpieces are obtained by using geometrical features gathered from the workpieces’ images, whereas in the CAD-based activities, the welding tasks are assigned to different mobile components of the welding torch; then, their welding paths are planned according to the workpieces’ CAD models. The vision & CAD interactive activities enable the mapping between the point cloud of a workpiece and its CAD model, so that the deviations caused by assembly errors can be detected and path compensation data can be determined. The effectiveness of the proposed hybrid offline programming method is demonstrated by integrating it into a subassembly welding robotic system. The experimental results indicate that this method can significantly improve the efficiency, accuracy, and flexibility of the robotic welding system.